2018
DOI: 10.1002/macp.201700620
|View full text |Cite
|
Sign up to set email alerts
|

Porous Vesicles with Extrusion‐Tunable Permeability and Pore Size from Mixed Solutions of PEO–PPO–PEO Triblock Copolymers

Abstract: Block copolymer (BC) vesicles in aqueous solution can encapsulate hydrophilic molecules or nanoparticles for drug and gene delivery, enhanced imaging, microreactors, or sensors. Inexpensive, biocompatible poly(ethylene oxide)–poly(propylene oxide)–poly(ethylene oxide) (PEO–PPO–PEO) triblock copolymers (TBCs) would be ideal for these applications if they could form concentrated vesicle solutions to encapsulate such molecules with high efficiency. It is shown that solutions of two PEO–PPO–PEO TBCs (EO5–PO68–EO5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
(134 reference statements)
0
3
0
Order By: Relevance
“… 42 The authors found that the mixture of copolymers in a 1 : 1 mass ratio generated the most stable polymeric capsules. However, the permeability of the structure was explored only later by Schantz et al 41 The authors prepared the exact vesicle solutions using a sequential extrusion of polycarbonate filters of different pore sizes from 2 to 0.1 μm. By loading molecules of different molecular weights, Schantz et al observed that the obtained capsules were porous and that the membrane's molecular weight cut-off was extrusion-tunable.…”
Section: Copolymer's Mixturesmentioning
confidence: 99%
See 2 more Smart Citations
“… 42 The authors found that the mixture of copolymers in a 1 : 1 mass ratio generated the most stable polymeric capsules. However, the permeability of the structure was explored only later by Schantz et al 41 The authors prepared the exact vesicle solutions using a sequential extrusion of polycarbonate filters of different pore sizes from 2 to 0.1 μm. By loading molecules of different molecular weights, Schantz et al observed that the obtained capsules were porous and that the membrane's molecular weight cut-off was extrusion-tunable.…”
Section: Copolymer's Mixturesmentioning
confidence: 99%
“…This p value alteration can be used as a strategy to modify the general permeability properties of the polymeric assemblies and rationally design porous carriers. The alteration of the copolymer selfassembly capabilities and consequent poration is generated by a change in the local copolymer membrane bending and B3 mm 5n m Polymerisation-induced self-assembly (PISA) 28 Micro-sized Micro-sized Polymerisation-induced phase separation (PIPS) 38,39 Micro-sized 200-300 nm 35 and from nano to micro size 36 Use of copolymer mixtures Di-block copolymers mixture 40 B150 nm 9-27 nm Tri-block copolymers mixture 41 B150 nm MWCO between 50 to 1000 Da (B1.1 to B2 nm) Di-block and tri-block copolymers mixture 43 B100 nm B5 nm Templated self-assembly strategies Soft templates 51 2-10 mm 100-200 nm Soft templates -pickering emulsion 56 B1 mm 150 nm Soft templates -HIPE 46 300-400 From nano to micro sized Solid templates 45 100 nm 3.5-4 nm Stimuli responsive poration Temperature 47 100-300 mm B10 mm Acoustic force 72 Micro-sized 100-200 nm Electric pulse 75,76 Micro-sized Nano-sized Transmembrane channels Protein membrane 79 Nano-sized MWCO o 400 Da (1-2 nm) DNA nanopores 82 B100 nm 2 nm Artificial channels 83…”
Section: Packing Parameter Variationmentioning
confidence: 99%
See 1 more Smart Citation